(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2014)
Research background. It is very important to recognize children whose motor development deviates from the normal, and it is affected or exposed to risk factors. The biggest attention should be paid on early diagnosis of motor development delay, and abilitation. This would let avoid severe impairments of motor development and complications. The aim of the study was to evaluate the impact of physiotherapy on motor development of infants of different gender, gestational age, height, weight, growing in infant home,. Research methods. Were analyzed motor development of 20 randomly selected infants (age 15.7 ± 10.25 weeks), growing in Klaipėda infant home. Subjects received physiotherapy with duration of 3 months. Munich functional developmental diagnostics scale was used to assess the development of three gross motor functions: crawling, sitting and walking. Research results. Before physiotherapy motor coefficient of about twenty percent of infants’ was rated < 50. Physiotherapy significantly (p < 0.05) improved infants’ gross motor functions: crawling, sitting and walking, and motor coefficient of the large majority of subjects after physiotherapy was rated as normal, i. e. > 70. There were no significant differences in motor coefficients between girls and boys. After physiotherapy motor coefficient of walking in full-term babies was significantly higher compared to preterm born babies (p < 0.05). Motor coefficient of sitting and walking in normal weight babies after physiotherapy was significantly higher (p < 0.05) compared to low weight babies. After physiotherapy motor coefficient of infants with different height improved significantly, but in taller babies it improved significantly more (p < 0.05) than in shorter babies. Conclusions. Applied physiotherapy significantly improved motor development of infants of different birth age, height and weight, growing in infant home. No significant differences in motor coefficients between girls and boys were identified. Birth age, height and weight are important for motor development. Keywords: physiotherapy, motor coefficient, birth, age, height, weight.